The Mission of the Church to People with Disabilities in Southern and Central Africa - Amanze, James N. (International review of mission, 2019)
Disability has, in recent years, become a focal point of discussion in many parts of the world with the increasing awareness that people with disabilities (PWDs) are disadvantaged because of their condition. Throughout history, PWDs have been relegated to the status of second-class citizens and in some instances treated inhumanly. In many cultures, particularly in Africa, issues of disability are surrounded by fear because of the strong belief that they are caused by sin, witchcraft, or evil spirits. People with mental challenges are demonized. This has led to a negative attitude toward PWDs in the world generally and in Southern and Central Africa in particular. This paper discusses the mission of the church in this context. It argues that the church must act as a catalyst for change by generating a positive attitude toward PWDs so that they can enjoy fullness of life. This can be achieved by mainstreaming issues of disability in the social, economic, political, and spiritual life of society as a whole.